Hajdamaky and Zamek kaniowski: two visions of Koliyivshchyna - Taudul, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article aims to analyse the theme of the Cossacks and the haidamaky, which was very present in the works of the great Ukrainian romantics, starting with Taras Shevchenko and Pantelejmon Kulish. It also became the object of poetic elaboration by various Polish poets including Juliusz Słowacki, and the lesser-known, but still interesting, Seweryn Goszczyński and Bohdan Zaleski. They became part of the so-called “Ukrainian school” of Polish Romanticism. In Poland, however, the poets did not interpret in a univocal way neither the historical role of the Sich of the Zaporozhye nor that of the haidamaky who sometimes appear as defenders of the faith and fighters for the independence of Ukraine, while in others they simply come into view as rebels and brigands, cruel and ruthless, who received for their actions the cruellest punishments. The author compares Haydamaky (Haidamaky, 1841) by Shevchenko and Zamek kaniowski (Kaniów Castle, 1828) byGoszczyński, because they describe the same story from 1768, the so-called Massacre of Humań, i.e. Koliyivshchyna, but with two different visions.